Inheritance Laws of Different Religions : Political Analysis of Islamic Law In indonesia - Zulkifli Nas (Albayan Journal of Islam and Muslim Societies, 2024)
Abstract: The situation of the condition of differences in the religion of heirs and experts becomes a problem in itself when implementing inheritance law for Muslim communities. The book of fiqh and the Compilation of Islamic Law (KHI) as a reference for Muslims in Indonesia explain that religious differences are a barrier to inherit each other. How is the politics of Islamic law in Indonesia to address this problem in a pluralist society? As Bagir Manan said, the politics of Islamic law is the formulation, implementation and renewal of law, so Islamic inheritance law is still implemented as stipulated in the Marriage Law, the Law on Religious Courts and also the Compilation of Islamic Law, where heirs and heirs of different religions do not inherit each other, it's just that to overcome the differences in religion of heirs and heirs, Islamic law reform is carried out through the development of the concept of mandatory wills produced by Ibn Hazm. The politics of Islamic law on inheritance law of different religions is implemented through the legal sources of jurisprudence. The decisions of the Religious Court and the Supreme Court of the Republic of Indonesia grant inheritance to heirs of different religions through mandatory wills, not through inheritance law. Abstrak: Situasi kondisi perbedaan agama ahli waris dan ahli menjadi masalah tersendiri ketika menerapkan hukum warisan bagi masyarakat muslim. Kitab fiqh dan Kompilasi Hukum Islam (KHI) sebagai acuan bagi umat Islam di Indonesia menjelaskan bahwa perbedaan agama merupakan penghalang untuk saling mewarisi. Bagaimana politik hukum Islam di Indonesia untuk mengatasi masalah ini dalam masyarakat yang pluralis? Seperti yang dikatakan Bagir Manan, politik hukum Islam adalah perumusan, implementasi dan pembaharuan hukum, sehingga hukum warisan Islam tetap diterapkan sebagaimana diatur dalam UU Perkawinan, Undang-Undang tentang Pengadilan Agama dan juga Kompilasi Hukum Islam, di mana ahli waris dan ahli waris yang berbeda agama tidak saling mewarisi, hanya saja untuk mengatasi perbedaan agama ahli waris dan ahli waris, Reformasi hukum Islam dilakukan melalui pengembangan konsep wasiat wajib yang dihasilkan oleh Ibnu Hazm. Politik hukum Islam tentang hukum warisan agama yang berbeda diimplementasikan melalui sumber-sumber hukum yurisprudensi. Putusan Pengadilan Agama dan Mahkamah Agung Republik Indonesia memberikan warisan kepada ahli waris yang berbeda agama melalui wasiat wajib, bukan melalui hukum warisan. Kata Kunci : Warisan, Hukum, Agama Berbeda, Analisis Politik, Islam